2009
DOI: 10.1016/j.febslet.2009.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of p53 in TPEN‐induced neuronal apoptosis

Abstract: a b s t r a c tDepletion of intracellular zinc with N,N,N 0 ,N 0 -tetrakis(2-pyridylmethyl)ethylenediamine (TPEN) induces protein synthesis-dependent apoptosis. In this study, we examined the requirement for p53 as an upstream transcription factor in TPEN-induced neuronal apoptosis. Chemical or genetic blockade of p53 markedly attenuated TPEN-induced neuronal apoptosis, while the stability and activity of p53 were increased by TPEN. In addition, expression of proapoptotic genes, PUMA and NOXA, and activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 23 publications
(49 reference statements)
6
37
0
Order By: Relevance
“…As a specific chelator of zinc, the pro-apoptotic effects of TPEN have been reported on several types of cells, including neuronal cells [49], prostate cancer cells [50], colon cancer cell [46], hepatocellular carcinoma cells [51] and breast cancer cells [52]. Mechanisms responsible for TPEN’s cytotoxicity vary in different cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…As a specific chelator of zinc, the pro-apoptotic effects of TPEN have been reported on several types of cells, including neuronal cells [49], prostate cancer cells [50], colon cancer cell [46], hepatocellular carcinoma cells [51] and breast cancer cells [52]. Mechanisms responsible for TPEN’s cytotoxicity vary in different cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures were prepared from mice on embryonic days 14e15 [3,5]. Dissociated cortical cells were plated onto 24-well poly-Llysine/laminin-coated plates (Nunc) in plating medium (Dulbecco's modified Eagle's medium [GibcoBRL], 20 mM glucose, 38 mM sodium bicarbonate, 2 mM glutamine, 5% fetal bovine serum, 5% horse serum [Cambrex Corp.]).…”
Section: Mouse Cortical Neuronal Culturesmentioning
confidence: 99%
“…Under normal conditions, intracellular zinc concentration is tightly regulated at very low (i.e., pM) levels (Bozym et al, 2006). Not only does the accumulation of excess zinc after ischemia, epileptic seizures, and traumatic brain injury lead to neuronal death (Choi and Koh, 1998), but the severe depletion of zinc also induces neuronal apoptosis (Ahn et al, 1998; Lee et al, 2008a; Ra et al, 2009). In addition to neurons, many other cell types also undergo apoptosis after zinc depletion (Makhov et al, 2008; McCabe et al, 1993; Wilson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that zinc chelation by N,N,N′,N′-tetrakis(2-pyridylmethyl)ethylenediamine (TPEN) induces p53-dependent apoptosis in cultured mouse cortical neurons (Ahn et al, 1998; Lee et al, 2008a; Ra et al, 2009). Furthermore, chemical or genetic blockade of p53 markedly attenuates this TPEN-induced neuronal apoptosis by blocking induction of proapoptotic proteins, including p53 up-regulated modulator of apoptosis (PUMA), NOXA, and caspase-11 (Ra et al, 2009).…”
Section: Introductionmentioning
confidence: 99%